Analysis of PARP inhibitor toxicity by multidimensional fluorescence microscopy reveals mechanisms of sensitivity and resistance - Michelena, Jone; Lezaja, Aleksandra; Teloni, Federico; Schmid, Thomas; Imhof, Ralph; Altmeyer, Matthias (Nature communications, 2018)
Exploiting the full potential of anti-cancer drugs necessitates a detailed understanding of their cytotoxic effects. While standard omics approaches are limited to cell population averages, emerging single cell techniques currently lack throughput and are not applicable for compound screens. Here, we employed a versatile and sensitive high-content microscopy-based approach to overcome these limitations and quantify multiple parameters of cytotoxicity at the single cell level and in a cell cycle resolved manner. Applied to PARP inhibitors (PARPi) this approach revealed an S-phase-specific DNA damage response after only 15 min, quantitatively differentiated responses to several clinically important PARPi, allowed for cell cycle resolved analyses of PARP trapping, and predicted conditions of PARPi hypersensitivity and resistance. The approach illuminates cellular mechanisms of drug synergism and, through a targeted multivariate screen, could identify a functional interaction between PARPi olaparib and NEDD8/SCF inhibition, which we show is dependent on PARP1 and linked to PARP1 trapping. Methods to study anti-cancer drugs cytotoxicity are often low throughput and rely on population average. Here the authors present an automated image-based cytometry method to quantify multiple cytotoxicity parameters in single cells, and use it to study the effect of PARP inhibitors in cancer cells.